A Unique Jew?: Judaism and Christology in Catholic and Protestant Theology - Gregerman, Adam (Studies in Christian-Jewish Relations, 2026)
If the risen Christ is unique—and every New Testament text and Christian theologian insists on this—it is only reasonable to expect the human Jesus the Jew was as well. This claim was historically sustained by deprecating first century Judaism and casting it as foil to Jesus in order to make him look distinctive and even unique. However, with the emergence of more favorable views of Second Temple Judaism, Christian scholars have increasingly situated Jesus within his Jewish milieu, not against it. But this introduces a profound question: If the historical Jesus was a Jew, and the historical Jesus should not be presented as remedying or standing apart from or superseding some purported fault(s) in Judaism, then how is Jesus the Jew distinctive or unique? I will look at attempts to grapple with this challenging question in writings of modern Protestants (Bible scholars Richard Hays and Christopher Hays) and Catholics (Pope Benedict XIV and selected Vatican statements). All the authors are committed to a fair presentation of Judaism but, when they try to establish Jesus’s uniqueness, some fail to live up to their own standards and fall back on unfavorable contrasts. Others eschew harsh contrasts but, struggling to insist on Jesus’s uniqueness, deploy vague comparisons that do not substantively engage the tensions in such claims.